2018
DOI: 10.1111/bju.14555
|View full text |Cite
|
Sign up to set email alerts
|

Tension‐free vaginal tape‐obturator for the treatment of stress urinary incontinence: a 12‐year prospective follow‐up

Abstract: Objective To evaluate the long‐term safety and effectiveness of inside–out transobturator tape (tension‐free vaginal tape‐obturator, TVT‐O) for the treatment of stress urinary incontinence (SUI). Patients and Methods Between August 2004 and August 2006, 87 consecutive patients with SUI who underwent TVT‐O were enrolled in this prospective cohort study. Patients with mixed UI, or pelvic organ prolapse requiring surgery, were excluded. Data relating to long‐term postoperative complications, subjective satisfacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…In our study, with increasing age and menopause duration, no patients reported OAB at the 2‐year follow‐up in the TVT‐O group, 3(9.7%) reported OAB at the 6‐year follow‐up, and 6(19.4%) reported it at the 10‐year follow‐up compared with none at the 2‐year follow‐up in the TVT‐S group and 1(3.0%) at the 6‐ and 10‐year follow‐ups, without significant differences ( P = 0.35; P = 0.05). In another TVT‐O 10‐year follow‐up study, the onset of de novo OAB symptoms was reported by 23 of 160 patients (14%), while in a 12‐year follow‐up, in which 73 patients (84%) were available for evaluation, OAB was observed in 12.3% of patients …”
Section: Discussionmentioning
confidence: 95%
“…In our study, with increasing age and menopause duration, no patients reported OAB at the 2‐year follow‐up in the TVT‐O group, 3(9.7%) reported OAB at the 6‐year follow‐up, and 6(19.4%) reported it at the 10‐year follow‐up compared with none at the 2‐year follow‐up in the TVT‐S group and 1(3.0%) at the 6‐ and 10‐year follow‐ups, without significant differences ( P = 0.35; P = 0.05). In another TVT‐O 10‐year follow‐up study, the onset of de novo OAB symptoms was reported by 23 of 160 patients (14%), while in a 12‐year follow‐up, in which 73 patients (84%) were available for evaluation, OAB was observed in 12.3% of patients …”
Section: Discussionmentioning
confidence: 95%
“…In addition, many studies supported the use of TO‐MUS, showing that transobturator insertion gives equivalent patient‐reported and clinician‐reported cure rates at short‐ and medium‐term follow‐up, compared with retropubic insertion 6‐8 . The long‐lasting benefits of transobturator route needed to be addressed, although recent studies with over 10 years follow‐up, reported excellent results in term of efficacy and safety 9,10 . The aim of the present prospective, multicenter study is to report, for the first time in the available literature, objective and subjective outcomes of women implanted with tension‐free vaginal tape‐obturator (TVT‐O) for pure SUI, at 13‐years follow‐up, to assess the long‐term efficacy, and the safety of this procedure.…”
Section: Introductionmentioning
confidence: 94%
“…[6][7][8] The long-lasting benefits of transobturator route needed to be addressed, although recent studies with over 10 years follow-up, reported excellent results in term of efficacy and safety. 9,10 The aim of the present prospective, multicenter study is to report, for the first time in the available literature, objective and subjective outcomes of women implanted with tensionfree vaginal tape-obturator (TVT-O) for pure SUI, at 13-years follow-up, to assess the long-term efficacy, and the safety of this procedure. We carefully studied in particular the incidence over the time of sling exposure.…”
Section: Introductionmentioning
confidence: 99%
“…6 In 2001, Delorme introduced the TOT procedure with the aim to avoid bladder, bowel, and major vascular injuries, reported with other retro-pubic sling techniques. 7 Numerous studies have compared the efficacy of Burch colposuspension and MUS. A meta-analysis of colposuspension and MUS demonstrated significantly higher overall and objective cure rates with MUS but a higher risk of bladder perforation in retropubic slings as compared to TOT.…”
Section: Internationalmentioning
confidence: 99%
“… 6 In 2001, Delorme introduced the TOT procedure with the aim to avoid bladder, bowel, and major vascular injuries, reported with other retro-pubic sling techniques. 7 …”
Section: Introductionmentioning
confidence: 99%